Analisis Distribusi Dosis Pada Terapi Alpha dengan Teknik Pencil Beam Scanning Pada Tumor Kraniofaringioma Menggunakan Software MCNP6 - Andina Riswandari Zulhiznaniyah; Riyatun; Suharyana (Jurnal Teori dan Aplikasi Fisika, 2025)
This study was conducted with simulation modeling on alpha therapy for the treatment of craniopharyngioma tumors using the reference head and neck phantom geometry from Lazarine (2006), which was equipped with spherical target cell geometry. The target cell geometry with a radius of 1.05 cm contains 27 partitions located at the base of the brain close to the spine. This simulation was performed using pencil beam scanning which has a beam size of 0.35 cm and was irradiated from the left direction as far as 25 cm from the skin surface by giving 5 variations of energy ranges 425, 430, 440, 445 and 450 MeV. The results of the simulation obtained an average absorbed dose of (1.30 ± 0.01) x 10-9 Gy/α with an isodosis rate of 62%. In addition, this study also takes into account the dose received by healthy cells around the tumor. The brain organ received the largest dose of (2.69 ± 0.01) x 10-13 Gy/α, when compared to the brain tumor cells received a dose of 0.021%. From the dose distribution to tumor cells, the irradiation time for craniofaringioma tumors is (13.3 ± 0.01) s with an α particle current of 1nA. Keywords: MCNP6, Alpha Therapy, Craniopharyngioma tumors, Pencil Beam.